PENGARUH PENDIDIKAN, PEKERJAAN DAN PENDAPATAN ORANG TUA TERHADAP PRESTASI BELAJAR EKONOMI PADA SISWA SMA - Hadiyanto, Herman (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2014)
This study aimed to determine the influence of parental education, occupation, and income on economic achievement; determine the influence of parental education, occupation and income simultan against economic achievement. This study used a quantitative approach, was analyzed by using the classical assumption test, multiple regression analysis with F test (simultaneous influence test) and t test (parsial influence test). The findings showed that parental education did not affect significantly on the achievement of economic, parental occupation and parental income affected significantly on the achievement of economic. As well as the variables of education, occupation and income of parents affected significantly oneconomic achievement